Incorporating professional recommendations into a graduate-level statistical consulting laboratory: A case study - Adam P. Sima; Viviana A. Rodriguez; Keighly E. Bradbrook; Brian S. DiPace; Victoria Okhomina (Journal of Clinical and Translational Science, 2021)
Abstract